1999
DOI: 10.1074/jbc.274.45.32279
|View full text |Cite
|
Sign up to set email alerts
|

A GCM Motif Protein Is Involved in Placenta-specific Expression of Human Aromatase Gene

Abstract: A new cis-element, trophoblast-specific element 2 (TSE2) is located in the placenta-specific enhancer of the human aromatase gene that dictates its tissue-specific expression. In the minimum enhancer region, an element similar to the trophoblast-specific element (TSE), originally described for the human chorionic gonadotropin ␣-subunit gene, also exists (Yamada, K., Harada, N., Honda, S., and Takagi, Y. (1995) J. Biol. Chem. 270, 25064 -25069). The co-presence of TSE and TSE2 is required to direct trophoblast-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 45 publications
4
48
0
Order By: Relevance
“…13 A GCM1-binding motif was also found in the promotor of the human chorionic gonadotropin a-subunit. 26 These findings support a complex and important role for GCM1 in placental maintenance and differentiation. GCM1 is differentially expressed in cytotrophoblasts destined for syncytial fusion in both mice 27 and humans.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…13 A GCM1-binding motif was also found in the promotor of the human chorionic gonadotropin a-subunit. 26 These findings support a complex and important role for GCM1 in placental maintenance and differentiation. GCM1 is differentially expressed in cytotrophoblasts destined for syncytial fusion in both mice 27 and humans.…”
Section: Discussionsupporting
confidence: 54%
“…At the transcriptional level, GCM1 was shown to be regulated by a functional cAMP-responsive element and a histone deacetylase 3-binding motif in the promoter region upstream of the start codon. 21,23,24 GCM1 was shown to regulate the expression of different proteins, such as the placental growth factor, 25 a human aromatase, 26 and the fusion protein, Syncytin1. 13 A GCM1-binding motif was also found in the promotor of the human chorionic gonadotropin a-subunit.…”
Section: Discussionmentioning
confidence: 99%
“…One of the native targets for Drosophila Gcm is the repo gene, which contains eleven Gcm-binding sites in its upstream region (Akiyama et al, 1996). Gcm-binding sites were also found in trophoblast-specific element 2 (TSE2), which is a ciselement that functions as a placenta-specific enhancer of the human aromatase gene (Yamada et al, 1999). In the present study, we demonstrated that ectopic expression of mouse Gcm1 in mouse fibroblasts led to the induction of the gene encoding the astrocyte-specific Ca 2+ -binding protein, S100β.…”
Section: Figmentioning
confidence: 99%
“…Abnormal development of placenta causes embryonic death in GCMa knockout mice (33). GCMa is also related to the control of placental functions by regulating gene expressions of aromatase, syncytin, and placental growth factor (8,37,40). Thus GCMa is essential for normal placental development and functions, and abnormalities in GCMa expression may be associated with pregnancy complications in humans, as decreased levels of GCMa expression have been reported in pre-eclampsia cases (4,9).…”
Section: Introductionmentioning
confidence: 99%